Brain-Computer Interfaces for Gait Rehabilitation After Stroke: A Scoping Review. - Mokienko, Olesya; Zisman, Maria; Bobrov, Pavel; Ustinova, Ksenia (American Journal of Physical Medicine & Rehabilitation, 2026)
Brain-computer interfaces (BCIs) represent a promising technology for restoring lower limb motor functions and gait after stroke. The application of BCIs in this field is supported by a limited number of studies. The objective of the review was to systematically and critically evaluate the current evidence on the use of BCIs for lower limb function rehabilitation in stroke patients. A systematic literature search was conducted in PubMed, Scopus, and Web of Science databases. The inclusion criteria were as follows: studies involving adult patients with poststroke hemiparesis; implementation of noninvasive BCIs specifically targeting lower limb rehabilitation; and detailed reporting of training protocols. Quality assessment was conducted using the National Institutes of Health Study Quality Assessment Tools. Twenty-two studies were included in the analysis with the following results. Electroencephalography-based BCIs integrated with functional electrical stimulation of muscles (EEG-BCI-FES) represent the most extensively investigated technology in this field, with efficacy and safety demonstrated in 3 randomized controlled trials (RCTs) and 1 non-RCT. BCI systems integrated with mechanical devices have been less studied, with evidence from 2 RCTs, while systems with only visual feedback have also been evaluated in 2 RCTs. For BCIs with exoskeletons, only technical feasibility has been demonstrated. Further research is needed to optimize training protocols and study the long-term effects of using BCI for rehabilitation.